Photosenzitizer dari Fraksi Metanol: N-Heksana Buah Cabe Merah (Capsiccum Annum L.) - Muh Shiddiq Maming; Aisyah Aisyah; Suriani Suriani; Iswadi Iswadi (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2017)
A research has been done on the dye components from the extract of red pepper (Capsiccum annum L) which is potentially used as photosensitizer. This study aims to determine the efficiency and the characteristics of the dye. The efficiency is measured on a cell made of glass ITO 100 Ω and a technical semiconductor TiO2. The pepper extract obtained from the ultrasonic maceration by methanol which then purified using a chromatography column using the ratio of 1: 4, 1: 1 and 4: 1 methanol:n-hexane. The results showed that the efficiency of the crude extract, fraction by ratio of 1:4; 1: 1 and 4: 1 are respectively 0.027%, 0.012%, 0.013% and 0.034%. Subsequently, the best efficiency fraction was characterized by using FTIR, UV-Vis and GC-MS. The wavelength of visible light obtained at 466 and 443 nm which is corresponds to the wavelength of carotene. The components indicate absorption at 1631.78 cm-1, 3008.95 cm-1 and 2992 cm-1 that are characteristic of carotenoid whereas, that of 1739 cm-1 and 3446.79 cm-1 are carbonyl and hydroxyl group of xantofil. According to the GC-MS fragmentation pattern, the carotenoid compounds identified by mass abundace at 91 and 105.